Nanomaterials : synthesis, characterization, and applications - Kalariakkal, Nandakumar; Haghi, A. K., editor; Zachariah, Ajesh K. 1983-, editor (Toronto ; Waretown, NJ : Apple Academic Press)
Includes bibliographical references and index